A New Iterative Method for the Approximate Solution of Klein-Gordon and Sine-Gordon Equations. (21st June 2022) - Fang, Jiahua; Nadeem, Muhammad; Habib, Mustafa; Karim, Shazia; Wahash, Hanan A.
Abstract : This article presents a new iterative method (NIM) for the investigation of the approximate solution of the Klein-Gordon and sine-Gordon equations. This approach is formulated on the combination of the Mohand transform and the homotopy perturbation method. Mohand transform (MT) is capable to handle the linear terms only, thus we introduce homotopy perturbation method (HPM) to tackle the nonlinear terms. This NIM derives the results in the form of a series solution. The proposed method emphasizes the stability of the derived solutions without any linearization, discretization, or hypothesis. Graphical representation and absolute error demonstrate the efficiency and authenticity of this scheme. Some numerical models are illustrated to show the compactness and reliability of this strategy.